2017
DOI: 10.7554/elife.24265
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor TFCP2L1 patterns cells in the mouse kidney collecting ducts

Abstract: Although most nephron segments contain one type of epithelial cell, the collecting ducts consists of at least two: intercalated (IC) and principal (PC) cells, which regulate acid-base and salt-water homeostasis, respectively. In adult kidneys, these cells are organized in rosettes suggesting functional interactions. Genetic studies in mouse revealed that transcription factor Tfcp2l1 coordinates IC and PC development. Tfcp2l1 induces the expression of IC specific genes, including specific H+-ATPase subunits and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
58
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 68 publications
7
58
0
Order By: Relevance
“…This suggests that cluster 8 is likely to be a transitional cell population and not a proliferating progenitor cell. Thus, in vivo lineage tagging analysis confirmed transitions of PC and IC cells not only during development (1517) but also in the adult collecting duct via a newly identified transitional cell type.…”
Section: Fluorescent Lineage Tracing Confirms Collecting Duct Cell Plmentioning
confidence: 60%
See 2 more Smart Citations
“…This suggests that cluster 8 is likely to be a transitional cell population and not a proliferating progenitor cell. Thus, in vivo lineage tagging analysis confirmed transitions of PC and IC cells not only during development (1517) but also in the adult collecting duct via a newly identified transitional cell type.…”
Section: Fluorescent Lineage Tracing Confirms Collecting Duct Cell Plmentioning
confidence: 60%
“…4C). This experimental model allowed us to study only the IC to PC transition occurring in adult mice as opposed to those occurring during embryogenesis (15). We found that NOTCH expression disrupted cellular patterning.…”
Section: Collecting Duct Cell Plasticity Driven By Notch Ligand Andmentioning
confidence: 99%
See 1 more Smart Citation
“…In kidney, cell type transition has been only studied in development and between subtypes of intercalated cells (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…The result of axial crease compaction and hence global volumetric compaction of ECM is a considerable increase in cell density from the as-patterned state -MDCK cells were initially distributed along prospective creases at an average spacing of ~30 µm, and condensed down to a spacing of 9.0 µm ± 12% CV (n = 10) after 40 hr. This spacing is approximately equivalent to the ~8 µm cell spacing seen in E18 mouse collecting ducts (28), and far closer than the ~17 µm spacing that would be expected purely due to cell proliferation over this time. In addition to axial crease compaction, the tight, ordered spacing of cells could be reinforced by axial cell migration along creases, and/or axially-biased cell intercalation (29) -mechanisms that we are currently examining.…”
Section: Resultsmentioning
confidence: 49%